Vitamin supplementation in oncological patients. Part I – B group vitamins - Badian, Magdalena; Dzierżanowski, Tomasz (Medycyna Paliatywna/Palliative Medicine, 2018)
Cancer patients often reach for unconventional medicine, and over two-thirds of patients use vitamin preparations. This paper presents B group vitamins regarding their demand for chronic disease, sources in the diet, as well as beneficial and unfavourable effects of their supplementation in cancer patients.